RANCANG BANGUN WEB PROFIL SEKOLAH SEBAGAI MEDIA PROMOSI SMP KARTIKA IV-10 SURABAYA - Robi Dwi Darmawan; Tauhid Nur Irawan; Shofiya Syidada (Melek IT : Information Technology Journal, 2022)
Information systems are widely used in an institution. For example in a company, office and education. In educational institutions this information system aims to promote or provide an overview of the profile of the relevant educational institution, administration, and other facilities. This website is the solution needed by SMP Kartika VI-10 which is located on Jl. Brawijaya No.38, Sawunggaling, Kec. Wonokromo, Surabaya City as a medium to introduce schools in the form of school profile information and also as an intermediary for students and parents to find out information on announcements, agendas or other school information. This study conducted to design and build a profile website that can apply information about school profiles and other information such as announcements, agendas, and news. The system is built using a system development life cycle approach where there are 5 stages, namely problem identification, requirements analysis, design, implementation and testing. Problem identification was carried out to collect data from observations and interviews. Requirements analysis was to find functional and non-functional requirements. System design, namely system models, database models and UI designs. The implementation is done by using HTML, PHP and MySQL. To testing the system is using the Blackbox method. The results of this study are a web profile for SMP Kartika 4-10 Surabaya which can display information about school profiles, announcements, agendas and information for new student registration.